Stylistic Analysis in Surah Al-Najm - Ziana Walidah; Muslim Yanuar; Dyah Nurul Azizah; Syihabuddin Qalyubi (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2020)
Stylistic is a multidisciplinary approach that aims to foreground the peculiar properties of texts on the basis of language and derive hidden and in-depth meaning to figure out major and minor themes. The evident fact that makes Stylistic a multidisciplinary approach is its retrievable, rigorous, and replicable principles. With Stylistic science, someone can reveal the secrets of the Qur’an as a whole by analyzing all aspects of the Qur’anic linguistics. This article aimed to analyze Surah al-Najm with the Stylistic theory. The research was qualitative research with library research or literature study. The analysis was carried out using an objective approach and descriptive analysis method by reading Surah al-Najm repeatedly then collecting relevant data. So, the data that has been found was analyzed with the two terms of Stylistics, they are semantics and imagery. From this study, it was concluded that in Surah al-Najm there were (1) nouns and verb preferences, various sentence structures and sentence confirmation in syntactic aspects, synonyms and antonyms in semantic aspects, and (2) several kinds of language styles such as isti'arah, majaz, and kinayah in imagery.